A morte de Vladimir Herzog e a luta contra a ditadura: a desconstrução do suicídio - Kleinas, Alberto (Universidade Federal de São Carlos, 2012)
The case Herzog had a strong impact on the recent political history of Brazil. A journalist killed on the premises of the 2nd. Army, in Sao Paulo, which was imposed by the establishment of suicide. Suicide wrought was challenged by his peers journalists, the Journalists' Union, the Archdiocese of St. Paul and in view of the pressures, the Jewish community of Sao Paulo. His burial was in an appropriate place for those who attempted against his life, and this burial and then act on Ecumenical Cathedral, are objects of this dissertation which seeks to clarify the reasons for this fact. As a Jewish collectivity could break with the collaboration and submission to the military regime, common in immigrant communities, and attest to the murder through the burial site of Vladimir Herzog. The contradictions and institutional pressures of Sao Paulo Jewish community demonstrate how external influence, Brazilian society was important in this episode, without underestimating the importance of individual people who were exposed to the truth and the struggle for democracy and human rights.
Death of Vladimir Herzog and the fight against dictatorship: a suicide deconstruction
Keywords: Ciência política; Brasil - transição política; Judaísmo; Direitos humanos; Vítimas de terrorismo do Estado; Democracia; Ditadura Militar; Mortos e Desaparecidos Políticos; Politics; Brazil; Judaism; Human rights; Democracy; Political transition; Military dictatorship; Political deaths and disappearances; CIENCIAS HUMANAS::CIENCIA POLITICA